Doctors and overpopulation 48 years later: a second notice - Greguš, Jan; Guillebaud, John (The European journal of contraception & reproductive health care, 2020)
Overpopulation exacerbates environmental and health problems, from climate change to biodiversity loss and pandemics. It is the 'upstream' driver of numerous existential threats. Addressing this compassionately - always - should be axiomatic for doctors. Our profession, by dramatically reducing death-rates since the 1800s while birth-rates remained high, sadly bears - unintendedly - some responsibility for the increase: one billion then, eight billion looming. Therefore, as doctors, we must surely be uniquely motivated to: be involved in rights-based policies and services with unbroken supply chains ensuring optimal contraceptive care being available to all couples worldwide, remove well-known tangible (contraceptives unavailable) and intangible (cultural, religious and mis-informational) barriers to women's choice to access family planning everywhere, while achieving full gender equity, especially in education, warn how overpopulation risks all planetary life, through optimal environmental education both for colleagues and the public, and campaign for a maximum of two children (replacement fertility - or less) on principle. Doctors and Overpopulation was established in 1972. Before and since, this issue has become taboo, still affecting many doctors and even people claiming to care passionately about a sustainable future: the environmental NGOs. Their silence implies conservation goals are achievable regardless of human numbers, while many studies show they are not. It is time for an open discussion about this taboo. Therefore we, concerned doctors of 2020, reiterate here the doctors' 48-year long cri de Coeur.
Keywords: Population Density; contraception; zdravotní politika; Climate Change; Birth Rate; dítě; klimatické změny; women’s health and rights; lékaři; lidé; environmental degradation; Contraception; climate change; pandemics; hustota populace; Physicians; Overpopulation; Health Policy; antikoncepce; porodnost; Child; population growth; family planning; Humans